A Cistercian Monk Writes to a Cistercian Nun: John Godard's Treatise for the Abbess of Tarrant, England, c.1250 - Freeman, Elizabeth (Cistercian studies quarterly, 2010)
The article offers information on the treatise wrote by Cistercian monk John Godard for the abbess of Tarrant, England in 1250. It mentions that the treatise focuses on the responsibility of a Cistercian monk in the spiritual development of Cistercian nuns. It notes that the treatise uses Pauline images, and the differences between the incorruptible and corruptible prize. It concludes that the treaties depict an example of reforms of nuns which is done in a pastoral way.